Evolutionary Game Analysis of Online Shopping Quality Control: The Roles of Risk Attitude and Government Supervision - Decheng Wen; Dongwei Yan; Xiaojing Sun; Xiao Chen (Complexity)
The product quality issues of online shopping have not been effectively solved with the rapid development of electronic commerce in China. Faced with the quality issues of online shopping, the main entities, such as online platforms and online sellers, should cooperate to control and assure compliant quality. The adverse selection of buyers caused by information asymmetry and the moral hazard of sellers aggravated by bilateral markets make the quality management of online shopping have a high degree of uncertainty and complexity. This study constructs an evolutionary game model to discuss the dynamic process of the quality behaviours of members and analyse the key triggers of the evolutionary directions in online shopping. By using numerical simulation analysis, the influences of government supervision intensities on the evolution trend of members’ quality behaviours are analysed with various risk attitude combinations in various cases. The current research finds that (1) the decrease of the quality control cost and the increase of the government’s benchmark fine are conducive to increasing the platform’s controlling probability; (2) the decrease of the proportion of rent and the increase of sellers’ fraud cost and the government’s benchmark fines are conducive to increasing the seller’s compliance probability; (3) when both the platform and seller are unwilling to make efforts for quality assurance, risk-seeking members make the seller gradually choose to provide compliant products; and (4) when the members are all risk-seeking, strengthening government supervision will help promote the transition of members’ behavioural choices in a benign direction. This paper enriches the theoretical research studies on both online product quality control and government-led social governance system of quality. Suggestions for government supervision and e-commerce entities are also provided for quality assurance and improvement.